Middle Anglo-Saxon Downham Road, Ely: extending the West Fen Road site. Issue 1 (2nd January 2020) - Cessford, Craig
ABSTRACT: The large Middle Anglo-Saxon site at West Fen Road, Ely, represents one of the most extensively investigated English archaeological sites of the long eighth century. Recent investigations have significantly expanded its known extent, providing important insights into the origins, development and the nature of the site and modifying previous interpretations. The evidence demonstrates the existence of three separate extensive areas of ditched enclosures used primarily for stock management dating to c . 720/50–825/50, although craft activities and occupation also took place. These enclosures were connected by a network of routeways and droveways and have extensive open areas between them, linked to arable agriculture. The scale of activity and evidence for grid planning indicate that this agriculture landscape was controlled by the contemporary monastic community at Ely.